2017
DOI: 10.1016/s2095-3119(16)61556-3
|View full text |Cite
|
Sign up to set email alerts
|

In vitro investigation of the effect of dairy propionibacteria on rumen pH, lactic acid and volatile fatty acids

Abstract: Ruminal acidosis is a prevalent disorder in ruminants such as dairy cows and feedlot beef cattle, caused primarily by the inclusion of a high percentage of readily fermentable concentrates in the diet. The disorder presents as an accumulation of lactic acid, a decrease of pH in the rumen and a subsequent imbalance of the rumen fermentation process with detrimental impacts on the animal's health and productivity. Dairy propionibacteria, a group of bacteria characterised by utilization of lactic acid as the favo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Caproiciproducens and Clostridium sensu stricto 12 are also significantly correlated with Acetobacter ( Supplementary Table S6 ), a genus characterized as an acetic acid producer ( Cleenwerck et al, 2002 ). Acidipropionibacterium, an apparent lactic utilizing bacteria ( Luo et al, 2017 ; Candry et al, 2020 ), correlated with Lactobacillus .…”
Section: Resultsmentioning
confidence: 97%
“…Caproiciproducens and Clostridium sensu stricto 12 are also significantly correlated with Acetobacter ( Supplementary Table S6 ), a genus characterized as an acetic acid producer ( Cleenwerck et al, 2002 ). Acidipropionibacterium, an apparent lactic utilizing bacteria ( Luo et al, 2017 ; Candry et al, 2020 ), correlated with Lactobacillus .…”
Section: Resultsmentioning
confidence: 97%
“…For the same reason, it seems unlikely that the increase in propionate observed when feeding P169 is produced by the strain P169 itself, since the recovery for this strain was 10 6 CFU per mL or lower (Peng et al, 2011). However, Luo et al (2017) showed that propionate can be formed by PAB at high rates and we cannot rule out that P169 could have produced propionate more rapidly in vivo than in vitro, as a result of the stimulation of natural microbial inhabitants of the rumen.…”
Section: Effects On Production Of Volatile Fatty Acids and Methanementioning
confidence: 85%
“…Previous studies found that PAB strains could increase rumen propionate levels (as a proportion of the total VFA) and lower levels of acetate in vivo (Stein et al, 2006;Raeth-Knight et al, 2007;Weiss et al, 2008) and in vitro (Akay & Dado, 2001;Alazzeh et al, 2013), suggesting that PAB could significantly contribute to rumen fermentation. Luo et al (2017) showed that PAB can degrade lactate in the rumen fluid in vitro. In experiments 1 and 2, the molar ratios of acetate to propionate in the controls were 4.0 and 4.6, respectively.…”
Section: Effects On Production Of Volatile Fatty Acids and Methanementioning
confidence: 99%
“…Higher lactic acid in rumen fluid trigger lactic acid utilizer growth. Some lactic acid utilizer such as Megasphaera elsdenii and Propionibacterium will consume lactic acid, leading to increased production of propionic acid (Seo et al, 2010;Luo et al, 2017). Increased propionic acid after inoculation of L. plantarum also reported by Weinberg et al (2003).…”
Section: Resultsmentioning
confidence: 93%